Partial recovery of vegetative state after a massive ischaemic stroke in a child with sickle cell anaemia. Issue 5 (5th May 2020) - Machado, Calixto; Rodríguez-Rojas, Rafael; Leisman, Gerry
Abstract : A 15-year-old patient with sickle cell disease with recessive homozygous haemoglobin S/HbSS suffered several crises developmentally after the last of which the patient fell into coma. CT scan then revealed a large infarct of the right cerebral hemisphere. Three weeks after the event, the patient began to demonstrate spontaneous eye opening and spastic quadriparesis with no evidence of command-following, gestural or verbal communication, visual pursuit or purposeful motor behaviour. Our case was in an 'unresponsive wakefulness syndrome' with atrophy of lateral and frontal regions of both hemispheres, demonstrated by MRI and preservation of circulation in the posterior arterial system, documented by MR angiography. Currently observed are spontaneous eye opening, preserved visual and auditory startle reflexes, normal brainstem reflexes, and grasp, palmomental and sucking reflexes. Our case demonstrates partial recovery of awareness with significant brain lesions, reflecting preserved brain activity as an indication of the modular nature of functional networks.